(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Web archiving is the process of collecting valuable content from the World Wide Web in a an archival format, to ensure the information can be managed independently and preserved for the general public, historians, researchers, and future generation. If the Web is not preserved, eventually valuable content will be lost forever. The Web is a very valuable source of information and several government and private institutions are involved in archiving parts of it for various purposes. This paper gives an overview of web archiving, describes the techniques used in web archiving, discusses some challenges encountered during web archiving and gives possible solutions to these challenges.